Γ-Aminobutyric Acid Is Synthesized and Released by the Endothelium: Potential Implications. Issue 5 (19th August 2016) - Sen, Suvajit; Roy, Sohini; Bandyopadhyay, Gautam; Scott, Bari; Xiao, Daliao; Ramadoss, Sivakumar; Mahata, Sushil K.; Chaudhuri, Gautam
Abstract : Rationale: : Gamma aminobutyric acid (GABA), a neurotransmitter of the central nervous system, is found in the systemic circulation of humans at a concentration between 0.5 and 3 μmol/L. However, the potential source of circulating GABA and its significance on the vascular system remains unknown. We hypothesized that endothelial cells (ECs) may synthesize and release GABA to modulate some functions in the EC and after its release into the circulation. Objective: : To assess whether GABA is synthesized and released by the EC and its potential functions. Methods and Results: : Utilizing the human umbilical vein ECs and aortic ECs, we demonstrated for the first time that ECs synthesize and release GABA from [1- 14 C]glutamate. Localization of GABA and the presence of the GABA-synthesizing enzyme, glutamic acid decarboxylase in EC were confirmed by immunostaining and immunoblot analysis, respectively. The presence of GABA was further confirmed by immunohistochemistry in the EC lining the human coronary vessel. EC-derived GABA regulated the key mechanisms of ATP synthesis, fatty acid, and pyruvate oxidation in EC. GABA protected EC by inhibiting the reactive oxygen species generation and prevented monocyte adhesion by attenuating vascular cell adhesion molecule -1 and monocyte chemoattractant protein-1 expressions. GABA had no relaxing effect on rat aortic rings. GABA exhibited a dose-dependent fall in blood pressure. However, the fall in BP was abolished after pretreatment with pentolinium. Conclusions: : Our findings indicate novel potential functions of endothelium-derived GABA. Abstract : Supplemental Digital Content is available in the text.